Remediation of Leakage through Annular Cement Using a Polymer Resin: A Laboratory Study. (January 2016) - Todorovic, Jelena; Raphaug, Martin; Lindeberg, Erik; Vrålstad, Torbjørn; Buddensiek, Maike-Liselotte
Abstract: Long term success of CO2 storage is heavily dependent on maintaining well integrity. Prevention and remediation of leakage through wells plays a crucial role in large scale implementation of CO2 storage. Squeeze cementing is the most common remediation practice in the oil and gas industry used for various well leakage scenarios. The objective of this work was to test the sealing ability of a commercially available temperature-activated polymer resin in a laboratory-scale squeeze cementing operation. Two well leakage scenarios were selected: micro-annuli or cracks in cement and debonding at cement-casing interface. Cement (with or without steel) core samples with designed vertical leak paths were prepared. Permeability of the samples was measured both before and after the squeeze procedure. Then the samples were disassembled and studied by optical microscopy. The squeeze procedure proved to be successful for plugging the designed leak paths.